HERO MOTOCORP LTD VERSUS TVS MOTORS COMPANY LTD: A FINANCIAL TEST DRIVE (CAHIERS MAGELLANES-NS, 2024)
Background: India is being the go-to market for many automobile industries in the world. Especially two-wheeler segments have a huge market in this country compared to any other. There are world’s leading scooter and motorcycle manufacturers based in India and operating across the globe. In this rapid growth of this sector, it is important and interesting to compare the financials of top two companies by using their financial statements and analyse the strength and weakness financially between them.Purpose: This study will analyse the Hero MotoCorp Ltd financials and the TVS Motors Company Ltd financials and compare them using various financial tools to find out the best in each aspect.Theoretical framework: The main drivers of the two wheel market in India are macroeconomic variables. The growth of India's economy and rising disposable income has enabled an expanding proportion of the population to buy their own transportation. The strong demand for two wheelers was a major factor in this. Income levels for the upper classes and urban populations have risen substantially as India's economy grows. This has led to increased purchasing power and a more willingness to spend on personal vehicle.Two wheelers are an efficient mode of transport, making them a popular choice for most people. The Hero MotoCorp Ltd and TVS Motor Company Ltd are mounting their revenues beyond Rs. 25000 crores for the financial year 2022-2023.Objectives: The primary objective is to compare the financials of Hero MotoCorp Ltd and TVS Motor Company Ltd by using their financial statements. Secondary objective is to annotate the financial position of Hero MotoCorp Ltd and TVS Motor Company Ltd using the various financial parameter and to decipher the financial analysis concept.Methodology:The article was done by equating the two companies for the five years from 2019 to 2023. The study is based on the financial and annual reports disclosed by the companies. To investigate the financial performance of Hero MotoCorp and TVS Motors various ratios and regression analysis were used.           Findings: By analysis the two automobile companies’ financial performance such as Hero MotoCorp and TVS Motors gives us vast amount of knowledge about their execution. The study was conducted using secondary data collected form annual reports, reputed journals and books. After the analysis of financial statements both the companies the performance of Hero Motors in higher than the TVS Motors. Even though the TVS Motors performance is lower than Hero MotoCorp the net profit, net sales, earnings per share, gross profit are in increasing trend and if the company puts more effort in attracting the investors it can improve the financial performance. Finally, after analysing the statements, it shows that the Hero MotoCorp performance is higher than the TVS Motors.